THE INCREASE OF COMPETITION IN RUSSIAN PUBLIC PROCUREMENT: THE SEARCH FOR SOLUTIONS IN THE RULES OF PROCEDURES - Dmitry Sergeevich Khvalynsky (Science and Innovation Center Publishing House, 2015)
The procurement activities of Russian government and municipal customers often arises the problem of choosing between splitting contracts in order to increase competition or attraction of large suppliers, known for the quality performance of its obligations, but not involved in petty trading. In order to solve the above problems the paper gives analysis of the effectiveness of the English auction used in Russian public procurement. One of the problems of the model is marked inability to complete the account the capacity of participants. In particular, participants are bidding solely on pre-formed combinations of goods, works and services under the contract. However, often there are situations when the price of goods, works and services depends on its number and combinations. Considering the above, the author offers a rebidding per unit stage or the transition to the use of auctions multiobject auctions recently developed by foreign researchers.